Kesejahteraan Pekerja, Analisis dari Status Pekerjaan dan Modal Sosial melalui Pasar Kerja - Rohmah, Rosyida Izzati; Rusdjijati, Retno; Murniningsih, Rochiyati (Fakultas Ekonomi Universitas Samudra, 2024)
The research aims to examine the influence of informal work and social capital on welfare mediated by the labor market. The cluster random sampling method was used to determine the sample, and 750 respondents were obtained. Research data was processed using SPSS and SmartPLS. The results show that informal workers and social capital have a simultaneous effect on well-being, while informal work is not proven to have an effect. Social capital is proven to have a positive effect on the labor market, and the labor market has a positive effect on welfare. The results of the indirect effect prove that informal work has a negative effect on well-being, while social capital has a positive effect on well-being.